SOSIALISASI DIGITAL MARKETING DAN PELATIHAN PEMBUATAN MASKER KAIN GUNA MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA MOJODOYONG KEDAWUNG KABUPATEN SRAGEN - Bambang Harjito; Afifah Ma’wa (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
The COVID-19 pandemic has created a global crisis in all aspects of life, one of which is in the economic sector. Many large companies decided to carry out massive layoffs which resulted in an increase in the unemployment rate in Indonesia. In addition, MSMEs in Indonesia have also experienced a decline in sales and even have to go out of business. This is relevant to the condition of some people in Mojodoyong Village, Kedawung, Sragen. A lot of residents of Mojodoyong Village were laid off and lost their jobs. MSMEs on convection and home tailors also experienced a decline in income due to a lack of jobs during the pandemic. This condition encourages us to help improve the economy of the residents of Mojodoyong Village. Team 388 of community service (KKN) UNS held digital marketing socialization and training in sewing cloth masks as an effort to empower the community during the pandemic. Digital marketing socialization was carried out offline and attended by 25 residents of MSMEs in Mojodoyong Village, while the training on making cloth masks was attended by 10 participants who did not have basic sewing skills. It is hoped that by holding digital marketing socialization and training to make cloth masks, Mojodoyong Village residents can understand the importance of digital marketing and have the ability to make and sell cloth masks so that they can become an additional source of income during the pandemic